A body of praise : understanding the role of our physical bodies in worship - Taylor, W. David O., 1972- (Grand Rapids, MI. Baker Academic., 2023)
"Leading Christian thinkers and practitioners cast a comprehensive vision for incorporating the arts into the life of the church"--
Includes bibliographical references and indexes.
Keywords: Worship; Public worship; Human body -- Religious aspects -- Christianity